Evaluation of Fine Needle Aspiration Cytology and Histopathological Correlation of Nodular Thyroid Lesions with Immunohistochemical Analysis - Laul, Abhishek Sanjay (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: Nodular lesions of the thyroid are common clinical findings, with fine needle aspiration cytology (FNAC) being the first-line diagnostic tool. Correlating cytological findings with histopathology and immunohistochemistry is essential for accurate diagnosis and management. Objective: This study aims to evaluate the efficacy of FNAC in diagnosing thyroid nodules by correlating cytological results with histopathological and immunohistochemical findings. Material and Methods: A cross-sectional study was conducted in the Department of Pathology at a tertiary care hospital over six months, including 120 patients with nodular thyroid lesions. Cytological smears were obtained via FNAC, followed by histopathological examination and immunohistochemical staining for markers such as Thyroid Transcription Factor-1 (TTF-1), Calcitonin, and Ki-67. Results: Out of 120 patients, 80% were diagnosed with benign lesions. Histopathological analysis revealed a significant correlation between cytological and histopathological diagnoses. Immunohistochemical markers demonstrated varying expression, aiding in the differentiation between benign and malignant lesions. Conclusion: FNAC is a reliable diagnostic method for thyroid nodules, and its correlation with histopathology and immunohistochemistry enhances diagnostic accuracy and guides appropriate management. Keywords: Thyroid nodules, fine needle aspiration cytology, histopathology, immunohistochemistry and TTF-1 and calcitonin